Integrating population-wide laboratory testing data with physician audit-andfeedback reports to improve glycemic and cholesterol control among Ontarians with diabetes. (2018) - Campitelli, Michael; Paterson, Michael; Azimaee, Mahmoud; Greenberg, Anna; Paprica, P. Alison; Schull, Michael; Victor, J. Charles; Kumar, Matthew; Shah, Baiju; Tu, Jack; Glazier, Rick
No abstract available